Post-Cardiac Injury Syndrome: Do we overlook its presence? A Case of Post-Pericardiotomy Syndrome and Current Update of its Management Strategy. - Ian Huang (Indonesia Journal of Chest Critical Emergency Medicine, 2019)
Abstract Introduction: Postcardiac injury syndrome (PCIS) is the term that encompasses of postpericardiotomy syndrome, postmyocardial infarction syndrome and post-traumatic pericarditis. The patient typically presents with fever, pericardial friction rub, and pericardial effusion with or without pleural effusion. The latency period between surgery and clinical manifestation greatly varied which not seldomly causing a delayed diagnosis of the disease. Case Report: Herein we report a 30-year-old woman with 1-year history of constrictive pericarditis who was scheduled for a pericardiectomy. She had a history a liver tuberculosis of which she was treated with oral antituberculous drug for 18 months. Her physical examination showed an increased jugular venous pressure with a positive Kussmaul’s Sign, cardiomegaly, and minimal bipedal pitting edema, with otherwise normal examination. Her transesophageal echocardiography (TEE) and MSCT cardiac were positive for constrictive pericarditis. The surgery was uneventful with 200 mL of serous pericardial fluid was removed. Ten days after the surgery, the patient complained fever with increased production of the drainage. She was then assessed as post pericardiotomy syndrome and was given high dose steroid. The drainage was gradually decreased and she was discharged after ten days with anti-inflammatory Conclusion:While PCIS is not uncommon, physicians practicing in the field of pulmonary and critical care medicine, and cardiac surgery should be aware not only the presence of this disease, but also to master its prevention and treatment.